Silsilah Raja-raja Sintang: Rekonstruksi sejarah awal Sintang dengan Genealogi - Yuda Benharry T., (Universiti Kebangsaan Malaysia, 2007)
This paper deals with how genealogy is used to reconstruct the history of Sintang, situated at the hinterland of Kapuas River in West Kalimantan. Some genealogical notes gathered have yielded interesting information on its development, especially the politics. Changes in the titles indicated interactions between this kingdom with the outside world. In addition, Sintang’s royal genealogy told the story of marital links she had with rulers from the surrounding regions. This paper proves that genealogy lend some support in reconstructing the past